A novel domino condensation—intramolecular nucleophilic cyclization approach toward annulated imidazo-pyrrolopyridines. Issue 46 (18th November 2015) - Voskressensky, Leonid G.; Storozhenko, Olga A.; Festa, Alexey A.; Khrustalev, Victor N.; Dang, Thi Tuyet Anh; Nguyen, Van Tuyen; Varlamov, Alexey V.
Graphical abstract: Abstract: A route for the synthesis of chromenes that are annulated with an imidazo[1, 2- a ]pyrrolo[2, 3- c ]pyridine core proceeding through a base-promoted domino reaction of 6-azaindole quaternary salts, has been developed.